syiah kuala university - Sundari sundariii (Universitas Syiah Kuala, 2019)
The art of dancing center is a place for human to do dance a ativities which are high nobility values expressed by body movements, it is clear that dance is related to movement. The aim of the signing art of dancing center are increasing awareness about dance in community and youth people and producing creative and qualified artists. For aesthetic beauty of buildings, such as facades and shapes, emphasizing the cultures of an area, expresing architecture used as the theme in designing the center. Applying theme in design is focus on style, shape, and the translation of local culture.